2013
DOI: 10.1186/1475-2891-12-135
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-measured waist and hip circumferences: results from a community study in Malaysia

Abstract: BackgroundMeasures of central adiposity are better predictors of adverse health events than BMI. Nonetheless, BMI is more widely used in health research. One reason for this may be the limited research supporting the self-measurement of waist and hip circumference. The lack of validity studies is particularly acute in Asia. The main objective was to establish the validity of self-measurement of waist and hip circumference in a community setting and the correlation of those measures with BMI, blood pressure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…In agreement with our findings, several previous studies have reported an overestimation of WC [10,15,16,18,33,34], but other studies have found an underestimation of selfmeasured WC compared with objectively measured WC [11][12][13][14]17,19,35,36]. Higher values of BMI [13,14,17] were associated with a higher degree of underestimation, with females underestimating more than males [17].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, several previous studies have reported an overestimation of WC [10,15,16,18,33,34], but other studies have found an underestimation of selfmeasured WC compared with objectively measured WC [11][12][13][14]17,19,35,36]. Higher values of BMI [13,14,17] were associated with a higher degree of underestimation, with females underestimating more than males [17].…”
Section: Discussionsupporting
confidence: 92%
“…Previously published research comparing precision of self-report vs trained-technician measurements indicate self-report measurements may be sufficiently accurate for epidemiological studies [ 33 35 , 38 , 42 , 43 ]. The few research studies available suggest that training, especially video instructions, have the potential to improve self-reported waist measurement accuracy [ 37 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, weight, height and WC were indicated by self-report of patients other than tool measuring, which may be biased [32]. However, previous studies have suggested that self-reported weight, height and WC have satisfactorily accurate for the assessment of the obesity status and have near-perfect correlations and agreement with measured anthropometric values [33,34]. Furthermore, BMI failed to distinguish between individuals with different types of fat distribution [35] and WC unable to distinguish persons with different height [36].…”
Section: Discussionmentioning
confidence: 99%